2010
DOI: 10.1266/ggs.85.87
|View full text |Cite
|
Sign up to set email alerts
|

Novel self-compatible lines of Brassica rapa L. isolated from the Japanese bulk-populations

Abstract: Self-incompatibility (SI) in Brassicaceae is sporophytically controlled by a single Slocus with multi allelic variety. The male S determinant, SP11/SCR (S-locus protein 11/S-locus cysteine-rich protein), is a small cysteine-rich protein, and the female S determinant, SRK (S-locus receptor kinase), functions as a receptor for SP11 at the surface of stigma papilla cells. Although a few of the following downstream factors in the SP11-SRK signaling cascade have been identified, a comprehensive understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Several genetic studies of the variation in strength of the SI response have been reported (Hatakeyama et al 2010; Isokawa et al 2010), suggesting that there are several genetic factors regulating SI strength in Brassica . From the viewpoint of incompatibility strength, UI described here has a strong incompatible response, the same as in the rigid SI phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic studies of the variation in strength of the SI response have been reported (Hatakeyama et al 2010; Isokawa et al 2010), suggesting that there are several genetic factors regulating SI strength in Brassica . From the viewpoint of incompatibility strength, UI described here has a strong incompatible response, the same as in the rigid SI phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the involvement of auxin in the regulation of self-incompatibility. Further analysis of mutants, either those that occur in natural populations (Isokawa et al 2010) or those induced by mutagenic treatments (Strickler et al 2013, Tantikanjana et al 2009) will no doubt identify new components of the SRK-mediated signaling pathway and clarify the mechanism of the self-incompatibility response.…”
Section: The Self-incompatibility Signaling Pathwaymentioning
confidence: 99%
“…Plant materials and observation of pollen tube behavior on the stigma An SC mutant line, TSC28, which was identified by screening Japanese bulk populations of B. rapa vegetable varieties and partially characterized as a novel SC mutant line that is independent from the S-locus or known SI-related genes (Isokawa et al, 2010), was used. As a reference B. rapa SI line, an inbred line, Chiifu-401 (Osaka et al, 2013), was used.…”
Section: Methodsmentioning
confidence: 99%
“…To identify all components of the SRK downstream pathway, alternative plant material and/or methodology is necessary. Previ-ously, we identified two novel SC mutant lines (TSC4 and TSC28) in B. rapa (Isokawa et al, 2010), from a screening of bulk populations of Japanese traditional and commercial B. rapa vegetables. The putative SC gene of TSC28 was mapped on linkage group A1, while S-locus, MLPK, ARC1 and THL were mapped on A7, A3, A4 and A6, respectively.…”
Section: Introductionmentioning
confidence: 99%